The great migration and the Democratic party : Black voters and the realignment of American politics in the 20th century - Grant, Keneshia Nicole, 1983- (Temple University Press, 2020)
"This book examines how the mass movement of African Americans from the South to the North from approximately 1915 to 1970--the movement commonly known as the Great Migration--helped change the relative positions and policy stances on racial politics for the major American political parties"--